2002
DOI: 10.1046/j.1464-410x.2002.02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin‐based fluorescence diagnosis of bladder carcinoma

Abstract: Objective To determine the use of hypericin instillation for the fluorescent detection of papillary bladder cancer and carcinoma in situ. Patients and methods Eighty-seven patients with papillary bladder cancer and/or carcinoma in situ received instillations with 40 mL of an 8 mmol/L hypericin solution for at least 2 h. Fluorescent excitation with blue light was effective for up to 16 h, and biopsies were examined by fluorescence microscopy. Results There were no side-effects reported, no photobleaching and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 21 publications
3
113
0
Order By: Relevance
“…As we reported previously, hypericin becomes concentrated specifically in bladder urothelial carcinoma lesions after instillation in humans (8,9). Due to this specific localization of hypericin in urothelial carcinoma lesions, the compound is used nowadays as a clinical diagnostic tool for the detection of superficial bladder tumors.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…As we reported previously, hypericin becomes concentrated specifically in bladder urothelial carcinoma lesions after instillation in humans (8,9). Due to this specific localization of hypericin in urothelial carcinoma lesions, the compound is used nowadays as a clinical diagnostic tool for the detection of superficial bladder tumors.…”
Section: Discussionmentioning
confidence: 58%
“…Hypericin is insoluble in water and plasma proteins were used as an effective hypericin carrier for incubation with multicellular tumor spheroids. For this purpose, the stock solution was diluted in an aqueous buffer containing plasma proteins, as reported previously (8,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that hypericin localizes in the neoplastic urothelium with higher specificity and selectivity to that displayed by aminolaevulinic acid, a precursor of the endogenous sensitizer protoporphyrin IX (D'Hallewin et al, 2002). Thus, besides its exploitation for accurate fluorescent detection of these malignancies, hypericin may become the photosensitizer of choice for PDT of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have limited ourselves by consideration of a spectral-selective case -luminescence of optically active porphyrins in biological tissues in red (λ f = 0.63…0.65 μm) region of spectrum [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The excitation of autofluorescence was realized using a blue solid-state laser with the wavelength λ = 0.405 μm that coincides with the porphyrins maximum absorption.…”
Section: Brief Theorymentioning
confidence: 99%